The relationship between timing of onset of menarche and depressive symptoms from adolescence to adulthood - C. Prince; C. Joinson; A. S. F. Kwong; A. Fraser; J. Heron (Epidemiology and Psychiatric Sciences, 2023)
Abstract Aims Girls who experience an earlier onset of menarche than their peers are at increased risk of depressive symptoms in mid-adolescence, but it is unclear if this association persists into adulthood. This study examines whether longitudinal patterns of depressive symptoms from adolescence to adulthood vary according to timing of menarche.